1990
DOI: 10.1093/oxfordjournals.jbchem.a123041
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Recombinant Human Interleukin 5 Produced by Chinese Hamster Ovary Cells

Abstract: The complete peptide map of purified recombinant human interleukin 5 (rhIL-5) was determined to verify its primary structure, glycosylation sites, and disulfide bonding structure. Each peptide fragment generated by Achromobacter protease I (API) digestion was purified and characterized by amino acid analysis and amino acid sequence analysis. After digestion with API, we could identify all the peptides which were expected from human IL-5 cDNA sequence. The analyses of sulfhydryl content in rhIL-5 molecule and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…The mechanism of unusual polymannosylation may be further elucidated by the construction of mutants glycosylated at a site other than position 49. Our previous result, that mutant lysozyme was glycosylated at a position in the most N-terminal site of the mutant proteins attempted in the experiment, supports the proposal that the efficiency of the glycosylation decreases with the distance of the N-terminus in proteins [4][5][6]. Therefore, we attempted to construct a mutant lysozyme having an N-glycosylation signal sequence at a more N-terminal site and on the molecular surface.…”
Section: Polymannosylationsupporting
confidence: 61%
“…The mechanism of unusual polymannosylation may be further elucidated by the construction of mutants glycosylated at a site other than position 49. Our previous result, that mutant lysozyme was glycosylated at a position in the most N-terminal site of the mutant proteins attempted in the experiment, supports the proposal that the efficiency of the glycosylation decreases with the distance of the N-terminus in proteins [4][5][6]. Therefore, we attempted to construct a mutant lysozyme having an N-glycosylation signal sequence at a more N-terminal site and on the molecular surface.…”
Section: Polymannosylationsupporting
confidence: 61%
“…29 Using size exclusion filtration, we demonstrated that immunoreactive IL-5 was completely detectable in a large-molecularweight fraction (>100 kd) after mepolizumab infusion. IL-5 is normally produced as a homodimer (estimated molecular weight is 52 kd), 30,31 and indeed, in control experiments both recombinant IL-5 and naturally produced IL-5 were detectable in the low-molecularweight fraction. To further elucidate the nature of high-molecular-weight immunoreactive IL-5 after mepolizumab therapy, we demonstrated that IL-5 was completely precipitated by means of incubation with protein A/G, thereby providing evidence that its high molecular weight was due to an immunoglobulin/IL-5 complex.…”
Section: Discussionmentioning
confidence: 87%
“…There are precedents for the antiparallel orientation of the monomeric chains of a dimer although there are none among the glycosyltransferases. Cys 42 and Cys 84 of one subunit of interleukin 5 are joined in an antiparallel manner to Cys 84 and Cys 42 of the other subunit (44,45). Similarly, the monomeric subunits of plateletderived growth factor are joined by two intermolecular disulfides between Cys 43 and Cys 52 to form an antiparallel arrangement (46,47).…”
mentioning
confidence: 99%